PENERAPAN METODE KANO PADA REDESAIN KEMASAN PRODUK KARAGENAN - Haslindah, Andi; Hanafie, Ahmad (LPPM-ITEBA, 2023)
Product development is a strategy and process carried out by companies in developing products, improving old products, or increasing the use of products to existing market segments with the assumption that consumers want new elements about the product. The aim of this research is to develop a good packaging design for carrageenan products using the Kano method. The method used in this study is the procedure for customer assistance for the development of cardboard packaging designs using the Kano method. The results of the research on the application of the canoe model and the two attributes fall into the Attractive category, so the packaging produced in this study is packaging made of aluminum foil, has a box shape, weighing 250 grams. Based on the priority of consumer needs to increase consumer satisfaction with packaging.